The Application of Psychoanalytic Counseling to Reduce Self-injury Behavior among High School Students - Prio Utomo; Endri Ardian (International Journal of Counseling and Psychotherapy, 2024)
Background: Self-injury behavior in adolescents, linked to emotional distress and trauma, is a growing concern. It can negatively impact academic performance and well-being during this critical developmental stage. Psychoanalytic counseling, which addresses unconscious processes and emotional conflicts, offers a unique approach to managing these behaviors. Objective: This study aims to examine the effectiveness of psychoanalytic counseling in reducing self-injury habits in high school students. This research was conducted at SMA Negeri 11 Bandung City. Method: This study uses a quasi-experimental approach. The instruments used include the Self Injury Questionnaire, Observation, and In-depth Interview: Psychoanalytic Counseling Evaluation Checklist. Data analysis used paired t-test and ANOVA statistical tests. Results: The results of the analysis yielded a Sig. (2-tailed) value of 0.002 <0.05, this means that psychoanalytic counseling is effective in reducing the habit of self-injury in high school students. Significant differences in pretest and posttest mean scores indicate that this approach can help students reduce self-injurious behavior. Conclusion: Schools can integrate psychoanalytic counseling as part of the guidance and counseling program to help students who experience self-injurious behavior. Contribution: The findings from this study can serve as a basis for schools to emphasize the importance of further mental health support. It may also influence the development of a mental health-based curriculum in secondary schools.